(3QaY GdedGeI YeG bjd aj GdMLGeIs - (3eMeO Hf Ydj Hf CMeO Hf Ydj Hf NeGQhjg Hf Whdhf GdOeTbqj GdUGdMj GdMfaj, TeS GdOjf , J (B953 (3g` s
(3ChdgG (B:s
(3hHYO agPG JYdjb SejJg QaY GdedGeI YeG bjd ai GdMLGeI hQJHJge Ydi CHhGH s
(3BNQgG (B:s
(3SeYJ MHjHi QShd Gddg Udi Gddg Ydjg hSde jbhd (B: (3GdefjI GdYdb ef dejfg GdYdb acQgJ EPG ONd aj fSH QShd Gddg Udi Gddg Ydjg hSdeJeJ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B291s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eLGejY JjehQ (B351) s
Keywords: (3GdMOjK h GdeUWdMs